2022
DOI: 10.1590/1414-431x2021e11850
|View full text |Cite
|
Sign up to set email alerts
|

The LDL/HDL ratio predicts long-term risk of coronary revascularization in ST-segment elevation myocardial infarction patients undergoing percutaneous coronary intervention: a cohort study

Abstract: Clinical indicators do not adequately predict the long-term prognosis of patients with ST-segment elevation myocardial infarction (STEMI) following percutaneous coronary intervention (PCI). The low-density lipoprotein (LDL)/high-density lipoprotein (HDL) ratio is expected to be a reliable predictor of the long-term prognosis of these patients. This study aimed to explore the correlation between the LDL/HDL ratio and long-term prognosis in STEMI patients undergoing PCI. Patients with confirmed STEMI who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…An elevated LDL-C to HDL-C ratio has been known as an important risk factor for coronary heart diseases [ 12 , 13 ]. The present study showed that increasing HP antibody titer was associated significantly higher ratio of LDL-C to HDL-C, which, to the best of our knowledge, has not been investigated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated LDL-C to HDL-C ratio has been known as an important risk factor for coronary heart diseases [ 12 , 13 ]. The present study showed that increasing HP antibody titer was associated significantly higher ratio of LDL-C to HDL-C, which, to the best of our knowledge, has not been investigated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…An increased LDL/HDL ratio was independently associated with long-term coronary revascularization in AMI patients. (22) The importance of lipid management in AMI patients has been mentioned in the guidelines of the European Society of Cardiology and the European Atherosclerosis Society, which recommend that strict management of LDL cholesterol with statins, ezetimibe, and proprotein convertase subtilisin/kexin type 9 inhibitors could reduce the cardiovascular risk. (23) Treatment of PD has been suggested to lower the LDL cholesterol and in ammatory markers, suggesting that an assessment of the PD and implementation of appropriate periodontal interventions in AMI patients might lead to a more effective lipid management.…”
Section: Discussionmentioning
confidence: 99%
“…STEMI also found to be associated with obesity and male gender and younger individuals al these results are in accordance with results of this study. 14,15 Risk factors are studied in this study on younger individuals of single tertiary care center in Islamabad, for better generalizability study can be conducted in multiple study settings across the country or regions and on a larger sample size. Study concluded that more male young adults were found to be having a STEMI, this could be because more male ratio of patients.…”
Section: Discussionmentioning
confidence: 99%